ETNOFARMAKOLOGI TUMBUHAN MIANA (Coleus scutellariodes (L.) Benth) PADA MASYARAKAT HALMAHERA BARAT, MALUKU UTARA - Anisatu Z. Wakhidah; Marina Silalahi (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2018)
Miana (Coleus scutellaroides (L.) Benth) is known as Mayana by local people west Halmahera. This plant is cultivated almost at every village in West Halmahera. After investigation, in fact the utilization of Miana as medicine has been implemented by almost local people west Halmahera. The aims of study are to record most utilization of Miana as medice at villages in west Halmahera and to explain about phytochemical of Miana which support its use as medicine based on the previous studies on pharmacology. Ethnobotanical data were collected from site at six villages, and then identified in plant herbarium laboratory. The result of study showed that Miana used to cure (disease; number of village) back pain because of menstruation (2), cough (2), ulcers (2), menstruation pain syndrome (1), bleeding after childbirth (1), appetie enhancer (1), dry lips (1), hemorrhoid (1), and increasing fertility (2). Based on these following the phytochemical content the Miana plant consists of essential oil, tannin, flavonoids, eugenol, steroid, saponins, fitol, rosmanic acid, streptozocin, and quersetin. Those phytochemcial content are strongly supposed playing as an important role in medicine because their pharmacologycal activities. In related to conservation, local people west Halmahera have been cultivating Miana at their homegarden till today. Keywords : Miana, Coleus scutellaroides (L.) Benth, etnofarmakologi, Halmahera Barat